(untitled) (Nuntius Antiquus, 2024)
This article argues that Xenophon’s conception of Socrates’ exemplary qualities, by which he sought to exonerate him of the charges of impiety and harming the youth, was not that of the average Athenian. The difference was such that someone who was pious in the way Xenophon represented Socrates as being might even appear to be impious to the majority of his fellow citizens. So too, what Xenophon described as Socrates’ benefits to others might have seemed quite otherwise, when measured by popular views. The article thus challenges the still prevailing image of Xenophon as a man of mediocre intelligence, who perhaps misunderstood Socrates, but was incapable of creating a picture of him that was coherent and informed by an original, and perhaps even accurate, vision of his teachings.